High-Impact Teaching Practices and Their Role in Enhancing Student Engagement in Physical Education Lessons - Soran, Entethar Faroq Allyas (Jurnal Ilmu Olahraga dan Kepelatihan Indonesia, 2026)
This study aimed to examine the extent to which high-impact teaching practices are implemented in physical education lessons and to assess the level of effective student engagement during these lessons, as well as to analyze the relationship between these practices and student participation. The research employed a descriptive method using survey and correlational approaches. The population consisted of physical education teachers in middle schools under the Nineveh Education Directorate, totaling 495 teachers across 324 schools. A sample of 217 teachers was selected and divided into three groups: an exploratory sample of 7 teachers, a preparation sample of 126 teachers, and a final application sample of 84 teachers. Data were collected using two questionnaires developed by the researcher, each consisting of 15 items. The first questionnaire measured the level of implementation of high-impact teaching practices in physical education lessons, while the second assessed the effectiveness of student engagement during the lessons. The collected data were analyzed using appropriate statistical techniques. The results indicated that the implementation of high-impact teaching practices in physical education lessons was at a moderate level. Similarly, the level of student engagement during physical education lessons was also found to be moderate according to teachers’ perspectives. In conclusion, the study highlights the need to improve the application of high-impact teaching practices to enhance effective student participation in physical education learning.